Difference in the Amount of Voltage between Solid and Liquid Form of Bilimbi Fruit as an Alternative Energy Source - Elisa (Journal of Technomaterial Physics, 2019)
The present study aimed to discover whether there was a difference in the amount of voltage between liquid bilimbi and fresh bilimbi fruit as an alternative energy source. The research samples were 100 grams of fresh bilimbi and 100 grams of liquid bilimbi. The samples were connected to a multimeter through zinc plate and copper plate using a crocodile clip cable. After connected, the voltage measurement of the bilimbi was carried out five times in order to obtain accurate data. The collected data were averaged, and the difference between the two samples was calculated. The results showed that the average amount of voltage from liquid bilimbi was 0.72 V while the average amount of voltage from fresh bilimbi was 1.42 V. Thus, the difference between the two forms of bilimbi was 0.7 V. In conclusion, there was a difference in the amount of voltage produced by liquid bilimbi and fresh bilimbi fruit as an alternative energy source in which fresh bilimbi fruit had a higher amount of voltage than the liquid bilimbi.